Solve for y 7(y-3)=4-(3y+5)

Math
7(y-3)=4-(3y+5)
Simplify 7(y-3).
Tap for more steps…
Apply the distributive property.
7y+7⋅-3=4-(3y+5)
Multiply 7 by -3.
7y-21=4-(3y+5)
7y-21=4-(3y+5)
Simplify 4-(3y+5).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
7y-21=4-(3y)-1⋅5
Multiply 3 by -1.
7y-21=4-3y-1⋅5
Multiply -1 by 5.
7y-21=4-3y-5
7y-21=4-3y-5
Subtract 5 from 4.
7y-21=-3y-1
7y-21=-3y-1
Move all terms containing y to the left side of the equation.
Tap for more steps…
Add 3y to both sides of the equation.
7y-21+3y=-1
Add 7y and 3y.
10y-21=-1
10y-21=-1
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 21 to both sides of the equation.
10y=-1+21
Add -1 and 21.
10y=20
10y=20
Divide each term by 10 and simplify.
Tap for more steps…
Divide each term in 10y=20 by 10.
10y10=2010
Cancel the common factor of 10.
Tap for more steps…
Cancel the common factor.
10y10=2010
Divide y by 1.
y=2010
y=2010
Divide 20 by 10.
y=2
y=2
Solve for y 7(y-3)=4-(3y+5)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top